Importance of the main chain of lysine for histone lysine methyltransferase catalysis. Issue 23 (28th May 2019) - Al Temimi, Abbas H. K.; Teeuwen, Ruben S.; Tran, Vu; Altunc, Arthur J.; Lenstra, Danny C.; Ren, Wansheng; Qian, Ping; Guo, Hong; Mecinović, Jasmin
Abstract : Enzymatic and computational studies on the simplest lysine analogues that possess a modified main chain demonstrate that the lysine's backbone contributes significantly to functional KMT binding and catalysis. Abstract : Histone lysine methyltransferases (KMTs) are biomedicinally important class of epigenetic enzymes that catalyse methylation of lysine residues in histones and other proteins. Enzymatic and computational studies on the simplest lysine analogues that possess a modified main chain demonstrate that the lysine's backbone contributes significantly to functional KMT binding and catalysis.